Yoga Sebagai Sarana Menuju Tuhan Yang Advaita - Ambarnuari, Mery; Widyawati, Anak Agung Ayu Alit (JURNAL YOGA DAN KESEHATAN, 2021)
Yoga is becoming an increasingly global activity. This worldwide yoga is only for hatha yoga, not accompanied by the well-known advanced stages of hatha yoga, namely Raja yoga. The actually, Yoga teach to connect Ätman and paramÄtman . This goal can be achieved if humans undergo the stages of yoga as a whole so that the atman who is affected by virtual nature can be purified again.Maha Rsi PÄtaÃ±jali was the first people to give an explanation of the yoga system in the Yoga Sutras and there are eight stages which are called astangga yoga. Furthermore, yoga teachings are also contained in tattwa texts, including: Lontar Text of Tattwa JÃ±Äna (prayogasaá¹…dhi);The lontar text of Wrhaspati Tattwa (á¹£aá¸anga yoga); Lontar text of JÃ±ÄnasiddhÃ¢nta (á¹£aá¸-aá¹…ga-yoga). Tattwa texts contain teachings about yoga because in the tattwa teachings there are the concepts of cetana and acetana. Putting off acetana leads to cetana with yoga as the path. The teachings of yoga whose aim is to connect and purify the Ätman to paramÄtmanÂ  are related to the advaita or monistic concept of divinity, because the paramÄtmanÂ  that the ÄtmanÂ  will aim at in yoga is of course the monistic paramÄtmanÂ  which believes that everything is God and all the differences that exist are mere delusion.